Never Give Up Attitude in the Novel of Negeri 5 Menara as A Reinforcement of the Pancasila Student Profile - Darmiyati; Mukti Widayati; Nurnaningsih Nurnaningsih (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2024)
This qualitative study explores the depiction of the